A biorefinery approach for spent coffee grounds valorization using pressurized fluid extraction to produce oil and bioproducts: A systematic review. (June 2022) - Araujo, Micheli Nolasco; dos Santos, Kallynca Carvalho; do Carmo Diniz, Natalia; de Carvalho, Júlio César; Corazza, Marcos L.
Abstract: Spent coffee grounds (SCG) is a promising feedstock to biorefinery implementation since this waste is low cost, a non-edible crop, and is generated in large amounts annually. In this review, we used the PRISMA approach to give an extensive overview of SCG oil extraction focusing on recent advances in pressurized fluid extraction (PFE) techniques. Low polarity solvents, as supercritical CO2, have presented lower recovery of total extracts (43.0–90.7% compared to Soxhlet extractions), total phenolics (64 mg GAE/100 g oil and 56.7 ± 2.3 mgCAE/gextract ), and higher diterpene content (75–107 mg/goil and 4.64%mol). While high-polarity solvents in pressurized liquids (PLE), for example, resulted in higher recovery (92.02–127.5%) and TPC (24.14 mgGAE/gdrySCG) . This review suggests that sequential PFE extraction is the best strategy to recover the biomolecules from SCG since this technique enhances the selectivity of the extraction process allowing to obtain different extract fractions with high content of target compounds. Graphical abstract: Unlabelled Image Highlights: Spent coffee grounds is a promising feedstock for oil production. Pressurized fluid extraction are emerging sustainable techniques to oil production. Viable biorefinery routes must integrate energy and bioactive compounds production. Recovery of bioactive compounds is crucial to biorefinery economic viability. Extraction as a first step enables prior and flexible recovery of bio-compounds.